Governor’s Award for restoration - Лидия Захарова; Алексей Поликарпочкин (Проект Байкал, 2023)
The Irkutsk Region Governor’s Award for Achievements in Culture and Art 2022 in the category “Works of Architecture, Urban Planning and Park Art” was awarded to the creative team consisting of Alexey Polikarpochkin, Maria Borisova, Lidia Zakharova, Evgeniya Kuznetsova and Alexandra Kushkova for the restoration of the cultural heritage sites in Irkutsk. The team of architects and restorers has completed more than 60 restoration projects over the last thirty years. Most of the projects have been realized.